FAKTOR YANG MEMPENGARUHI PERKEMBANGAN MORAL PESERTA DIDIK DI SMA NEGERI 1 RANAH BATAHAN KABUPATEN PASAMAN BARAT - Yanra, Nefri; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
This research moved from the phenomena in field because the persistence of students who commit acts of immorality. Based on this study the researchers raised issues: what are the factors that influence moral development of the students in SMA Negeri 1 Ranah Batahan. The research objective is to describe: 1) Internal factors that influence moral development of students in SMA Negeri 1 Ranah Batahan. 2) External factors that influence moral development of students in SMA Negeri 1 Ranah Batahan. The population is all students in SMA Negeri 1 Ranah Batahan as many as 470 students. Techniques that used in sampling is stratifiedrandomsampling, sample zise83 of 470 students. Instrumentused inthis studywas a questionnaire.The results of this reseachrevealedthat: 1) Internalfactorsthatinfluencemoral developmentof studentsinSMA Negeri1 RanahBatahanas much as90.85% verymuchin thiscategory. 2) Externalfactorsthatinfluence moral developmentof studentsinSMA Negeri1 RanahBatahanas much as90.96% verymuchin thiscategory. The reseachersuggest studentstobe able tochooseandmaintainandto improve themoralbehaviormoral developmentthat developsat anystage of development.